Ray Donovan. Season seven [videorecording (DVD)]. - Schreiber, Liev; Voight, Jon, 1938-; Marsan, Eddie; Mihok, Dash, 1974- (Paramount : Showtime, 2020)
While Ray makes progress in therapy, there are dangers from the past that require the Ray Donovan of old. Between NYC mayor Ed Feratti, an unrelenting NYPD officer hunting for the truth and clients old and new, Ray struggles to find the balance between fixing for clients and fixing himself. And when Feratti's corruption brings a piece of Mickey's past back to New York, Ray is forced to seek answers to long-buried questions.